(untitled) (Research, Society and Development, 2022)
Financial Education goes beyond a boring theory applied to students, it must show reality and how to deal with it in the day-to-day life of children or adolescents, it differs from superficial classes during mathematics teaching. If applied correctly, it results in a society aware of how to invest its money, whether in basic things such as the monthly purchase in a supermarket or which stock exchange action would be interesting to apply its income. This work seeks to show how this education has been treated by the government and how it has been applied. As a result, the main research sources were sites such as the OECD (Organization for Economic Co-operation and Development) and also the ENEF (National Strategy for Financial Education).